A rapid flow assessment tool for automated dry fibre preforms – a numerical and experimental study - Shafique, Usman (2022)
Automated dry fibre placement (ADFP) has gained the attention of the aerospace industry in the past few years. The preforms produced by ADFP are manufactured into composite parts by liquid composite moulding (LCM) processes. In contrast to manual preforming, this automated process reduces the required time and improves quality of layup. Whereas, LCM offers low cost manufacturing, making it an excellent selection when producing large parts. Due to high compaction of unidirectional fibres during the deposition process and binder presence, the preforms are produced with high fibre volume fractions. This decreases the permeability of these preforms and effects the overall fill time during LCM. During the deposition process defects are induced into the preforms from machine inaccuracy, variability in material and poor adhesion. This results in the formation of inter-tow or inter-course gaps and overlaps.